Information technology and indigenous people - Dyson, Laurel Evelyn 1952-; Hendriks, Max A. N.; Grant, Stephen 1965- (Hershey, Pennsylvania Information Science Pub., 2007)
"This book provides theoretical and empirical information related to the planning and execution of IT projects aimed at serving indigenous people. It explores cultural concerns with IT implementation, including language issues & questions of cultural appropriateness"--Provided by publisher.
Preface -- Section I: Indigenous people and information technology: issues and perspectives -- Section II: Technology in education -- Section III: Cultural preservation and revitalization -- Section IV: Applications transforming communities -- Section V: Linking communities and improving access -- Epilogue -- Future directions -- Glossary -- About the authors -- Index.
Keywords: Indigenous peoples -- Computer network resources; Information technology -- Social aspects; Internet -- Cross-cultural studies; Electronic books